Comparative analysis of the effect of PO administered acid suppressants on gastric pH in healthy cats. (4th September 2020) - Ryan, Phillip; Odunayo, Adesola; Price, Josh; Hecht, Silke; Hillsman, Shanna; Galyon, Gina; Steiner, Joerg; Tolbert, M. Katherine
Abstract: Background: Proton pump inhibitors (PPIs) are among the most commonly prescribed medications for esophagitis and upper gastrointestinal erosion and ulceration in cats. Newer PPIs such as lansoprazole and esomeprazole are believed to be effective in cats, but the effect of many of these PPIs on gastric pH in cats has not been explored. Hypothesis/Objectives: To evaluate the efficacy of PO esomeprazole, dexlansoprazole, and lansoprazole on intragastric pH in healthy cats. We hypothesized that esomeprazole and lansoprazole would provide superior acid suppression compared to dexlansoprazole and reach pH goals extrapolated from people for the treatment of esophagitis and duodenal ulceration. Animals: Twelve healthy research cats. Methods: Randomized, 3‐way crossover study. Cats were given esomeprazole and lansoprazole at a dosage of 1 mg/kg PO q12h or dexlansoprazole at 6 mg/kg PO q12h. Intragastric pH was recorded at baseline and for 4 days of treatment. Mean pH and the mean percentage time (MPT) intragastric pH was ≥3 or ≥4 were compared among and within treatment groups. Results: Cats treated with lansoprazole had a lower MPT ± SD of intragastric pH ≥3 (8.8 ± 6.8%) and mean ± SD pH (1.6 ± 0.5) than did cats treated with dexlansoprazole (41.2 ± 34.6% and 3.11 ± 1.6, respectively) or esomeprazole (54 ± 33.8% and 4.1 ± 3.9, respectively; P  ≤ .04). Esomeprazole was the only treatment that achieved the goals defined for people for the treatment of duodenal ulceration by Day 4 of treatment (MPT ± SD of intragastric pH ≥4 of 77.1 ± 29.2%). Conclusions and Clinical Importance: Orally administered esomeprazole might be a superior acid suppressant in cats compared to PO lansoprazole or dexlansoprazole.